Characterization and Synthesis of Biomaterials - - 5, Theme (Recent Research in Science and Technology, 2010)
Proceedings of "Conference on Recent Advances in Biomaterials Dec 17-18 ’10" Held at Saveetha School of Engineering, Saveetha University, Thandalam, Chennai-602 105, Tamilnadu, India Theme 5 Characterization and Synthesis of Biomaterials